Learning Qawaid Through Language Game Adlif Kalimatan for Students of Arabic Language and Literature at UIN Maulana Malik Ibrahim Malang - Muassomah Muassomah; Ma’rifatul Munjiah (Arabic Education Program IAIN Pekalongan, 2019)
Qawaid is an element of Arabic that must be mastered by Arabic language learners, including students of the Department of Arabic Language and Literature of UIN Maulana Malik Ibrahim Malang, though it is still seen difficult until today. The learning of qawaid that has been running so far relies on traditional methods and strategies, i.e. the deductive method (tariqah qiyasiyah) and inductive (tariqah istiqra'iyyah). It is done by asking the students to write sentences (jumlah mufidah) on a sheet or assignment book. This study aims to explore a strategy of language game named adlif kalimatan (add one word) in learning qawaid in the said department. It is a case study and uses a qualitative approach. Data collection is carried out from observation, interviews and documentation. The results of this study indicate that the language game of adlif kalimatan is able to make instructional activity more interesting and is able to motivate students to apply qawaid in speaking and writing skills.